Two-Beam Free-Electron Lasers and Self-Injected Nonlinear Harmonic Generation - Elio Sabia; Emanuele Di Palma; Giuseppe Dattoli (Applied Sciences, 2021)
The possibility of extending the tunability of Free-Electron Lasers towards short wavelengths has been explored through the design of devices conceived to enhance the mechanisms of nonlinear harmonic generation. In this respect, different schemes of operation have been suggested in the past, such as harmonic seeding, bi-harmonic undulators, and two-beam self-seeding devices. In this paper, we discuss how these methods can be merged into a tool, extending the performance of FEL devices.